LEARNERS INDEPENDENCE MATCHING INDIVIDUAL STRATEGIES AND LEARNING STYLES THROUGH LANGUAGE ACTIVITIES ON THE INTERNET - Aida GJINALI; Sonila PIRI (Association of Social and Educational Innovation, 2023)
Glotodidactics, based on the central role of the student, suggests that teacher select didactic concepts that lead to the improvement of knowledge of the language being studied. Observing students' behaviors enables the acquisition of cognitive competences about study skills, strategies and features in learning. Today, learners' independence is given great importance in the teaching process. In order to achieve this objective, the instructor's contribution is fundamental; the instructor must act to determine and develop, in cooperation with the student, the mechanisms and approaches, such as learning strategies, but also the selection of appropriate tools. The use of the Internet offers various alternatives for the acquisition of new linguistic inputs, respecting the peculiarities and personal strategies in learning. This study analyzes manners and objectives that can be achieved in the acquisition of the Italian language through activities developed on the Internet, matching individual strategies or characteristic features that are applied in learning a foreign language.